2020
DOI: 10.1186/s13071-020-04312-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvum upregulates miR-942-5p expression in HCT-8 cells via TLR2/TLR4-NF-κB signaling

Abstract: Background: Micro (mi)RNAs are small noncoding RNA molecules that function in RNA silencing and post-transcriptional regulation of gene expression. This study investigated host miRNA activity in the innate immune response to Cryptosporidium parvum infection. Methods: In vitro infection model adopts HCT-8 human ileocecal adenocarcinoma cells infected with C. parvum. The expression of miR-942-5p was estimated using quantitative real-time polymerase chain reaction (qPCR). The TLRs-NF-κB signaling was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For instance, the activation of NF-κB signaling, coupled with the induction of B7-H1 by downregulation of miR-513 in Cryptosporidium infected cells may contribute to the apoptotic resistance of infected cells ( Gong et al, 2010 ). Consistently, a genome-wide miRNA expression analysis showed significant modulation of miRNA expression profile of miR-942 in C. parvum gastro-intestinal epithelial cells through the activation of the TLR4/NF-κB pathway ( Zhang et al, 2020a , Zhang et al, 2020b ). On the other hand, as explained above, the expression of chemokines as CCL20 can be downregulated by the infection.…”
Section: Modulation Of the Immune Response And Apoptosis Pathwaysmentioning
confidence: 62%
See 1 more Smart Citation
“…For instance, the activation of NF-κB signaling, coupled with the induction of B7-H1 by downregulation of miR-513 in Cryptosporidium infected cells may contribute to the apoptotic resistance of infected cells ( Gong et al, 2010 ). Consistently, a genome-wide miRNA expression analysis showed significant modulation of miRNA expression profile of miR-942 in C. parvum gastro-intestinal epithelial cells through the activation of the TLR4/NF-κB pathway ( Zhang et al, 2020a , Zhang et al, 2020b ). On the other hand, as explained above, the expression of chemokines as CCL20 can be downregulated by the infection.…”
Section: Modulation Of the Immune Response And Apoptosis Pathwaysmentioning
confidence: 62%
“…( Kumar et al, 2018 ), 17. ( Zhang et al, 2020a , Zhang et al, 2020b ), 18. ( Zhou et al, 2009 ), 19.…”
Section: Molecular Factors Involved In Cryptosporidium ...mentioning
confidence: 99%
“…To test this hypothesis, we transfected siRNA-IFI27 into HCT-8 cells and infected the cells with C. parvum. The infected cells were treated with various concentrations of recombinant TRAIL (10,25, and 50 ng/ ml). After 6 h, the cell apoptosis ratio was assessed in all cultures.…”
Section: Ifi27 Induces Cellular Apoptosis Through the Trai/ Trail-med...mentioning
confidence: 99%
“…Our previous study of miRNA expression in HCT-8 cells infected with C. parvum found that miR-942-5p, miR-181d, miR-3976, miR-18b-3p, miR-34b-5p, and miR-3591-3p may regulate apoptosis during the early phase of infection [ 24 ]. In a more recent study, we showed that C. parvum upregulated miR-942-5p expression in HCT-8 cells via the Toll-like receptor (TLR) 2/TLR4-NF-κB signaling pathway [ 25 ]. The present study investigated the mechanism of miR-942-5p in regulating HCT-8 cell apoptosis triggered by C. parvum infection, namely that the upregulation of miR-942-5p decreased HCT-8 cell apoptosis by targeting the IFI27 gene via the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) pathway and protected C. parvum from being cleared during the early stage of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptosporidiosis, caused by Cryptosporidium spp., is an important zoonotic parasitic disease, seriously threatening the health of humans and many animals [ 1 , 2 ]. Considering that the severity of cryptosporidiosis is closely associated with host status, especially immunity, understanding the host response to infection is critical to effectively develop well-directed control strategies against cryptosporidiosis [ 3 ].…”
Section: To the Editormentioning
confidence: 99%